불확실성에 대한 인내력 부족과 걱정의 관계에서 자기자비의 매개효과 - 우재연(Jaeyeon Woo); 현명호(Myoung-Ho Hyun) (Seuteureseu yeon-gu (Online), 2020)
본 연구는 불확실성에 대한 인내력 부족과 걱정의 관계에서 자기자비의 매개효과를 확인하고자 20대남녀 203명에게 불확실성에 대한 인내력 부족, 걱정, 자기자비를 측정하고 이를 분석하였다. 그 결과, 자기자비는 불확실성에 대한 인내력 부족과 걱정의 관계를 매개하였다. 또한 자기자비의 하위요인 중 자기친절과 보편적 인간성의 간접효과가 가장 큰 것으로 나타났다. 이는 불확실성에 대한 인내력이 부족할 경우고통스러운 상황에서 자기 자신에게 자비로운 태도로 반응하는 것이 어려우며 이것이 과도한 걱정으로 이어질 수 있음을 의미한다. 본 연구의 결과는 불확실한 상황을 감내하는 힘이 부족하여 과도하게 걱정하는사람을 대상으로 자기자비를 증진시키는 개입이 유용할 수 있음을 시사한다. Background: Pathological worry is frequently associated with intolerance of uncertainty. The purpose of this study is to investigate the mediating effect of self-compassion in the relationship between intolerance of uncertainty and worry. Methods: A total of 203 participants (male N=64, female N=149, mean age: 22.18 years) completed the questionnaires measuring levels of intolerance of uncertainty, worry, and self-compassion. Results: Data from this study show that self-compassion partially mediated the relationship between intolerance of uncertainty and worry. In addition, mediation models by sub-factors of self-compassion were tested, and it was analyzed that the most effective mediator was self-kindness and common humanity. Conclusions: Based on the results of this study, it was confirmed that intolerance of uncertainty could inhibit self-compassion, which leads to an increase in worry. Therefore, intervention and dealing with self-compassion in the treatment of pathological worry and generalized anxiety disorder are important. KCI Citation Count: 1